Exploring the Reproductive Health Education of Health Service Professionals in Mogadishu, Somalia - Yalahow, Abdiasis (Université d'Ottawa / University of Ottawa, 2017)
Somalia has recently come out of a two decade long civil war and is currently in a post-war and rebuilding phase. The national health system, largely crippled during years of conflict, is faced with a significant maternal mortality ratio and the debilitating effects of a high fertility rate. To combat these issues, the new Somali government is working toward creating a strong national health system that addresses some of these key indicators. With a lack of human resources in healthcare and the need for better reproductive health services, the need to invest in educating a new generation of health service professionals is evident. To address this gap in education, many educational institutions with health science faculties have opened in the last decade but the quality and accuracy of their curricula has yet to be examined. My thesis addresses this gap in knowledge. Through a multi-methods study that included reviewing curricula and curricular materials, conducting key informant interviews, and facilitating focus group discussions, I was able to learn about the quality and comprehensiveness of reproductive health topics in health service professionals‟ education and training. Religion, culture, logistical issues, and lack of oversight shape the way reproductive health is taught to health students. This study provides an important foundation to help inform key stakeholders working to improve the Somali health system.
Keywords: Reproductive Health; Somalia; Post Conflict; Fragile State; Higher Education